1993
DOI: 10.1039/p19930001563
|View full text |Cite
|
Sign up to set email alerts
|

New oxetane-type taxanes from Taxus wallichiana Zucc.

Abstract: The needles of Taxus wallichiana Zucc. gave the novel oxetane-type taxane diterpenoids 2 and 5, whose structures have been established on the basis of spectroscopic data and chemical reactions. The acidcatalysed rearrangement of 1 0-deacetyl baccatin I I I has been investigated.As part of a study on renewable sources of taxol and related compounds, we reported the isolation of 14-f3-hydroxy-10deacetylbaccatin I11 1 from the needles of the Himalayan yew (Tuxus wullichiunu Zucc.).' Compound 1 can be used as a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…[3,4] Much less is known about the anionic rearrangements of this type of compounds, [5] as well as about their photochemical behaviour. [6,7] To complement previous studies on the cationic rearrangements of medium-sized terpenoids, [8,[9][10][11] we have now investigated the behaviour of the enone 2 toward bases and light, supporting the experimental results with X-ray crystal structure data and theoretical molecular dynamics (MD) and quantum chemical calculations.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…[3,4] Much less is known about the anionic rearrangements of this type of compounds, [5] as well as about their photochemical behaviour. [6,7] To complement previous studies on the cationic rearrangements of medium-sized terpenoids, [8,[9][10][11] we have now investigated the behaviour of the enone 2 toward bases and light, supporting the experimental results with X-ray crystal structure data and theoretical molecular dynamics (MD) and quantum chemical calculations.…”
Section: Introductionsupporting
confidence: 66%
“…The presence of a ketone carbonyl group was viewed as critical for induction of anionic and photochemical behaviour. Ketone 2 emerged as a suitable substrate because of its availability in multigram amounts by modification of the natural product hallerin (1) [8,10] and the presence of the reactive 1,4-diene system.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift of C-1 at C 59.4, an unusual downfield chemical shift for an unoxygenated quaternary carbon, together with the absence of long-range correlation between C-11 and C-16/C-17, 7) strongly indicated that taxane 2 possessed an 11(15!1) rearranged skeleton, i.e., a brevifoliol analogue. 9) This conclusion was further confirmed by the observation of long-range correlation from H-10 to C-1 in the HMBC data. The assignment of functional groups was started with the signal at 2.27 (1H, d, J ¼ 7:4 Hz), typical of an H-3 ring junction proton.…”
mentioning
confidence: 60%
“…As with other terpenoids, Wagner-Meerwein rearrangement occurs to the Α-ring of taxoids bearing a tertiary hydroxyl group at C-l (33)(34)(35). Kingston and his collaborators (33) found that treatment of the 7, 2'-(9-diprotected paclitaxel derivative with mesyl chloride and subsequent deprotection led to the Α-ring contracted derivative 18 which possesses an antitubulin activity similar to that of paclitaxel (33).…”
Section: α-Ring Contracted Taxoids From 10-deacetylbaccatin IIImentioning
confidence: 88%
“…On the other hand, compound 20 and 21 were obtained after treatment of 10-deacetylbaccatin ΙΠ with /rara-toluene sulfonic acid in methanol (35).…”
Section: α-Ring Contracted Taxoids From 10-deacetylbaccatin IIImentioning
confidence: 99%